Pengaruh Kompetensi Terhadap Kinerja Karyawan pada PT. Satria Jaya Sentosa Kabupaten Kolaka - Hasriani; M. Ilham Wardhana Haeruddin; M. Ikhwan Maulana Haeruddin; Chalid Imran Musa; Tenri Sayu Puspitaningsi Dipoatmodjo (PT Maju Malaqbi Makkarana, 2023)
The purpose of this research is to determine the competency of employee performance at PT Satria Jaya Sentosa, Kolaka Regency. The independent variable in this research is competency while the dependent variable is employee performance. The population in this study was all employees at PT Satria Jaya Sentosa, namely 70 people, while the sample in this study was 70 people using saturated sampling techniques. This research uses a quantitative approach and is analyzed using a simple linear regression analysis method using SPSS 24.00. The data processed is the result of distributing questionnaires from 70 employees of PT. Satria Jaya Sentosa, Kolaka Regency. Based on the research results, it shows that there is a significant influence between competence on the performance of PT employees. Satria Jaya Sentosa, Kolaka Regency with a coefficient value of 0.666 (positive value) and tcount of 8.129 > 1.668 (ttable), it can be concluded that Competency (X) has a positive and significant effect on employee performance (Y) and a sig value of 0.000 < 0.05. The coefficient of determination value is 0.493 or 49.3%.